ANALISIS HUKUM PEMBERIAN LISENSI WAJIB PATEN DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA DI INDONESIA - Nender, Clarita; Engeline Pijoh, Feibe; Novy Tuwaidan, Arthur (At-Tanwir Law Review, 2025)
Patent, as one form of intellectual property rights, possesses an exclusive and monopolistic nature that can stimulate innovation, but may also cause market distortions if misused. In this context, compulsory licensing serves as a legal mechanism to balance the exclusive rights of patent holders with public interest, particularly in the health sector. This study aims to analyze the issuance of compulsory patent licenses from the perspective of competition law in Indonesia. The research method employed is normative juridical, using statutory and doctrinal approaches. The findings indicate that although the regulation of compulsory licensing has been accommodated in the Patent Law and is in line with TRIPs provisions, its implementation still faces several challenges, such as the lack of derivative regulations, technological field discrimination, and weak prioritization of national interests. A case study of the Indonesian Competition Commission (KPPU) decision and the compulsory licensing policy for HIV/AIDS drugs demonstrates that this mechanism is essential for maintaining fair business competition and ensuring public access to technological innovations